Wiskott–Aldrich syndrome protein deficiency in natural killer and dendritic cells affects antitumor immunity. Issue 4 (13th January 2014) - Catucci, Marco; Zanoni, Ivan; Draghici, Elena; Bosticardo, Marita; Castiello, Maria C.; Venturini, Massimo; Cesana, Daniela; Montini, Eugenio; Ponzoni, Maurilio; Granucci, Francesca; Villa, Anna
<x xml:space="preserve">Abstract</x> Wiskott–Aldrich syndrome (WAS) is a primary immunodeficiency caused by reduced or absent expression of the WAS protein (WASP). WAS patients are affected by microthrombocytopenia, recurrent infections, eczema, autoimmune diseases, and malignancies. Although immune deficiency has been proposed to play a role in tumor pathogenesis, there is little evidence on the correlation between immune cell defects and tumor susceptibility. Taking advantage of a tumor‐prone model, we show that the lack of WASP induces early tumor onset because of defective immune surveillance. Consistently, the B16 melanoma model shows that tumor growth and the number of lung metastases are increased in the absence of WASP. We then investigated the in vivo contribution of Was−/− NK cells and DCs in controlling B16 melanoma development. We found fewer B16 metastases developed in the lungs of Was−/− mice that had received WT NK cells as compared with mice bearing Was−/− NK cells. Furthermore, we demonstrated that Was−/− DCs were less efficient in inducing NK‐cell activation in vitro and in vivo. In summary, for the first time, we demonstrate in in vivo models that WASP deficiency affects resistance to tumor and causes impairment in the antitumor capacity of NK cells and DCs.